2020
DOI: 10.1111/odi.13575
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of NRAGE promotes autophagy‐related gene expression and the periodontitis process in mice

Abstract: Background and Objective Neurotrophin receptor‐interacting MAGE homologue (NRAGE) plays a crucial role in the regulation of bone metabolism. The present study investigated the regulation role of NRAGE on autophagy activation and periodontitis process during experimental periodontitis. Materials and Methods Six‐week‐old wild‐type (WT) and NRAGE−/− mice were randomly divided into three time points in the periodontitis groups (0, 2, and 4 weeks). Histopathological changes were determined using the tooth mobility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Neurotrophin receptor-interacting MAGE homologue (NRAGE)-deficient mice with ligature-induced periodontitis exhibited severe alveolar bone loss compared to control mice. Knockout of NRAGE induced autophagy-related gene expression and accelerated bone destruction by increasing the activity and differentiation of osteoclasts [51].…”
Section: Osteoclastsmentioning
confidence: 99%
“…Neurotrophin receptor-interacting MAGE homologue (NRAGE)-deficient mice with ligature-induced periodontitis exhibited severe alveolar bone loss compared to control mice. Knockout of NRAGE induced autophagy-related gene expression and accelerated bone destruction by increasing the activity and differentiation of osteoclasts [51].…”
Section: Osteoclastsmentioning
confidence: 99%
“…A study by Liu at el. showed that the knockdown of Mage-D1 induced autophagy-related gene expression and boosted the process of periodontitis by enhancing osteoclast activity and differentiation 23 . Therefore, we boldly speculate that the role of Mage-D1 in osteogenesis varies with cell type, which suggesting the complex and diverse roles of Mage-D1 in osteogenesis and odontogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent studies further con rmed that Mage-D1 inhibits the NF-κB signalling pathway by combining with IκB kinase β (IKKβ) 22 , which is a vital regulator of odontoblast differentiation. Liu et al showed that knocking out Mage-D1 can induce the expression of autophagy-related genes by enhancing the activity and differentiation of osteoclasts, thereby accelerating the process of periodontitis 23 . Our previous studies have shown that Mage-D1 could affect the bone differentiation ability of rat EMSCs by binding to p75NTR 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It encodes an 86-KDa protein and is a member of the Type II MAGE family, comprising 778 amino acids (aa), of which the MAGE homology domain is common for MAGE family members and the interspersed repeat domain (IRD) is relatively unique to NRAGE for no homology to any public specific protein. These features imply that there are both uniform and specific characteristics of NRAGE compared with other members of the MAGE family (33)(34)(35)(36). Growing evidence confirmed that NRAGE functions as a transcriptional regulator mediating multiple signaling pathways from apoptosis (16,(18)(19)(20), cell differentiation (37)(38)(39), cell cycle distribution (26), cell adhesion (40), and angiogenesis (22).…”
Section: Discussionmentioning
confidence: 98%